IN VITRO CULTURE OF ORCHIDS: THE ROLES OF CLASS-1 KNOX GENE IN SHOOT DEVELOPMENT - Endang Semiarti; Aziz Purwantoro; Ari Indrianto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2014)
In vitro culture of orchids has been developed for many purposes. Some native orchids and commercial orchid hybrids are propagated using seed germination or cut explants such as leaves, shoot tips, and roots to produce large numbers of orchid plantlets. This technique is widely used for the purpose in conservation of natural orchid species and industry of commercial orchid hybrids. However, the molecular genetic mechanism behind growth and development of these orchids during in vitro culture is still unclear, and needs to be elaborated. Recent advanced in transgenic technology in orchid is very helpful for studying the mechanism of action of key genes in various stages of orchid development during in vitro culture. In this review, an attempt to understand the role of class-1 KNOX gene and its relationship with other genes in the initiation of shoot apical meristem (SAM) for shoot development from orchid protocorm (a tubercle of developing orchid embryo) and PLBs (Protocorm Like Bodies) during in vitro culture will be discussed. It will answer the question about how the shoot formation can be controlled during growth and development of orchid cells in in vitro culture.